2018
DOI: 10.1177/0958305x18759177
|View full text |Cite
|
Sign up to set email alerts
|

Economic and environmental implications of the recent energy transition on South Korea’s electricity sector

Abstract: South Korea’s electricity sector is at a crossroads. A transition to a safer and more ecologically friendly electricity system, one that would reduce dependence on coal and nuclear power plants and produce more electricity from new and renewable energy, is being suggested and actively discussed. Changes to these two pillars of the electricity sector, which have enabled a reliable and affordable electricity supply, present environmental and economic concerns. Will this shift adversely affect the electricity sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…In South Korea, nuclear power was introduced in 1978 to meet electricity demand, which was increasing in line with rapid economic growth. Nuclear power was promoted as an important pillar of South Korean energy policy, along with coal-fired power [5]. At the end of 2018, there were 24 nuclear plants operating in South Korea; they had a total capacity of 22.5 GW [6].…”
Section: Energy Transition Policies and Nuclear Industry Sectors In Smentioning
confidence: 99%
“…In South Korea, nuclear power was introduced in 1978 to meet electricity demand, which was increasing in line with rapid economic growth. Nuclear power was promoted as an important pillar of South Korean energy policy, along with coal-fired power [5]. At the end of 2018, there were 24 nuclear plants operating in South Korea; they had a total capacity of 22.5 GW [6].…”
Section: Energy Transition Policies and Nuclear Industry Sectors In Smentioning
confidence: 99%
“…The central approaches to reach this goal are renewable energy development and energy efficiency improvement. 33 They include various technical and policy innovations, such as electric vehicles, smart meters, carbon pricing, and emissions trading.…”
Section: Energy Transitionmentioning
confidence: 99%
“…Energy equity deals with the accessibility and affordability of energy supply across the population. 35 Stakeholder participation policies encourage citizens to join community energy initiatives or projects (e.g., Kim 33 and Mundaca et al 36 ). To successfully reach a low-carbon future, innovations are necessary for both policies and technologies.…”
Section: Energy Transitionmentioning
confidence: 99%
“…It was found that the discounted cumulative costs from 2009 to 2050 in the SS scenario would be 20% and 10% higher than in the BL and GP scenarios, respectively. Kim 17 constructed nine scenarios that reflect changes in South Korea 's energy policy and analyzed the environmental and economic impacts of the South Korean power sector using LEAP. Despite using very conservative assumptions about the generation of renewable energy, the study found a more economically feasible pathway that would yield less GHG emissions than the baseline scenario.…”
Section: Literature Reviewmentioning
confidence: 99%